Radicalization and variations of violence: new theoretical approaches and original case studies - Beck, Daniel; Renner, Julia (Contributions to International Relations, 2023)
Foreword -- Chapter 1 Introduction -- Part I: Causes and the Constitution of Radicalization -- Chapter 2 Organising Political Violence: Radicalisation and militancy as narrative activity -- Chapter 3 Making Sense of Terrorism and Violence A Case Study -- Chapter 4 Correlates for Foreign Fighters in Tunisia. Protest and Marginalization as predictors for Foreign Fighter mobilization? -- Part II: Approaches to prognosis, de-radicalization and prevention -- Chapter 5 Radicalization and Public Discourse. Government Narratives in Reaction to Terrorist Attacks and their Relevance in Addressing and Preventing Violent Extremism -- Chapter 6 The (non-)escalation of violence during the third Act of the Yellow Vests protests. A critique of interactionist theories of violence -- Chapter 7 Elicitive Peace Education in Polarizing Conflicts over Democracy: A Relational Perspective Complementing Prevention of Radicalization -- Part III: Selected Case Studies of Radicalization -- Chapter 8 Representation of Kurdish Female Combatants in Western Cinema. A Frame Analysis of Fiction Films on Female Combatants -- Chapter 9 Manifestations of Violence in the Causality of a Radicalization Episode. A Case Study on The Margins of La Paz-Bolivia -- Chapter 10 Radical Politics in Post-conflict Settings -- Chapter 11 Conclusion. .